2020
DOI: 10.1200/jco.2020.38.6_suppl.119
|View full text |Cite
|
Sign up to set email alerts
|

TALAPRO-1: A phase II study of talazoparib (TALA) in men with DNA damage repair mutations (DDRmut) and metastatic castration-resistant prostate cancer (mCRPC)—First interim analysis (IA).

Abstract: 119 Background: Phase 2 and 3 studies with poly(ADP-ribose) polymerase inhibitors (PARPi) have demonstrated antitumor activity in patients (pts) with mCRPC with DDRmut who were previously treated with novel hormonal therapy (NHT). We report the first IA of a Phase 2 study of TALA, a potent inhibitor and trapper of PARP. Methods: TALAPRO-1 (NCT03148795) is enrolling pts (N ≈ 100) with measurable soft tissue disease, progressive mCRPC, and DDRmut likely to sensitize to PARPi (including ATM, ATR, BRCA1, BRCA2, C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
21
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 39 publications
(22 citation statements)
references
References 0 publications
0
21
1
Order By: Relevance
“…One avenue is on targeting DDRd. Besides platinum compounds, PARPi have shown very promising results in Phase 1 and 2 trials 21‐23 . Recently, these findings were validated in the Phase III PROfound trial 2 .…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…One avenue is on targeting DDRd. Besides platinum compounds, PARPi have shown very promising results in Phase 1 and 2 trials 21‐23 . Recently, these findings were validated in the Phase III PROfound trial 2 .…”
Section: Discussionmentioning
confidence: 92%
“…PARPi have shown very promising results in Phase 1 and 2 trials. [21][22][23] Recently, these findings were validated in the Phase III PROfound 26,27 Although not yet confirmed in a clinical setting, PTEN alterations in an in vitro setting appear to influence homologous repair, in such a way that PTEN-deficient prostate cancer cells are susceptible to treatment with PARPi. 28,29 Moreover, a preclinical study demonstrated in vitro and in vivo, that a senescence response to PARPi triggered by PTEN deficiency in prostate cancer cells, transformed to apoptosis in case of additional p53 dysfunction.…”
Section: Discussionmentioning
confidence: 98%
“…One milligram of talazoparib daily is being tested in the open-label phase II trial TALAPRO-1 (NCT03148795) in patients with mCRPC with mutations in ATM , ATR , BRCA1 , BRCA2 , CHEK2 , FANCA , MLH1 , MRE11A , NBN , PALB2 , or RAD51C who progressed despite androgen-receptor-targeted therapy and taxane-based chemotherapy [ 54 ]. Preliminary data for 43 patients (20 BRCA1/2 , 14 ATM , 2 PALB2 , 7 other) showed an overall response rate of 25.6% (13.5–41.2), with an ORR of 50% (27.2–72.8) in the BRCA1/2 subgroup and 7.1% (0.2–33.9) in the ATM subgroup.…”
Section: Other Parp Inhibitors In Prostate Cancermentioning
confidence: 99%
“…Talazoparib (oral 1 mg, once daily [QD]) is approved in the US, EU, and other countries as monotherapy for the treatment of patients with human epidermal growth factor receptor 2 (HER2)-negative advanced breast cancer with a germline BRCA 1/2 mutation [12,13], and is under investigation in other tumor types [14,15]. Findings from the phase 3 EMBRACA trial demonstrated that treatment with talazoparib 1 mg QD signi cantly improved progression-free survival (hazard ratio [HR] 0.54 [95% con dence interval (CI)] 0.41 to 0.71; P < 0.001) and patient-reported outcomes compared with chemotherapy in patients with HER2negative advanced breast cancer and a germline BRCA1/2 mutation [16,17].…”
Section: Introductionmentioning
confidence: 99%